KEDUDUKAN WANITA DALAM MASYARAKAT TIONGKOK KUNO: STUDI KASUS FILM MULAN - Yusuf Arifin, Yohan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The position of women in the structure of ancient Chinese society is very interestingto discuss, this is because traditions in China prioritized the position of men in allaspects of life in Chinese society at that time. This research uses Mulan movie as aresearch object to explain the position of women in ancient Chinese society. Thisresearch is a qualitative descriptive study that uses Mulan movie as referencematerial and is supported by other references related to the topic of this research.From the research results, it was found that the position of women in the life ofancient Chinese society was quite low, this was because there were many thingsthat cornered women at that time, and also the discrimination they experiencedwhere men were given priority over women. It is hoped that this research can provideadditional references for those who wish to study Chinese culture and history,especially the position of women in ancient Chinese society.